Biodegradable plastics from marine biomass: A solution to marine plastic pollution - Khan, Nida; Sudhakar, Kumarasamy; Rizalman, Mamat (Elsevier Ltd, 2025)
The growing demand for plastics has raised environmental concerns due to their non-biodegradable nature. Sustainable solutions are urgently required to decrease plastic pollution. This study explored the potential of Sargassum wightii, a seaweed found in Malaysia, as a sustainable material for bioplastic films. The seaweed-based bioplastic was produced using an extraction-based method where alginate was formed using NaOH, followed by mixing sodium alginate with isopropanol and potato starch. The bioplastic was then characterized using various analytical techniques, including Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), and Fourier-Transform Infrared (FTIR) spectroscopy. Physical properties such as density and moisture content, along with environmental tests like water absorption and biodegradability, were evaluated. TGA analysis indicated that 31.12 % of the sample remained as residue. FTIR spectroscopy identified the presence of bioactive compounds, with a prominent alcohol group peak at 3358cm-1. XRD analysis revealed a peak at 23.1°, indicating crystallinity within the sample. The moisture content of the bioplastic film was found to be 21.16 %. The water absorption test demonstrated the film's hydrophilic nature, showing a 60 % increase in weight. A soil burial test for biodegradability confirmed a 40 % reduction in weight over 21 days, indicating a reasonable degradation rate. These findings suggest that seaweed holds promise as an alternative raw material for bioplastic production, contributing to more sustainable materials and reducing reliance on non-biodegradable plastics.